2011
DOI: 10.1186/1423-0127-18-35
|View full text |Cite
|
Sign up to set email alerts
|

MiR-204 regulates cardiomyocyte autophagy induced by ischemia-reperfusion through LC3-II

Abstract: BackgroundAutophagy plays a significant role in myocardial ischemia-reperfusion (IR) injury. So it is important to inhibit autophagy to protect cardiomyocytes besides anti-apoptosis. MiRNA has been demonstrated to protect cardiomyocytes against apoptosis during IR, while whether it has anti-autophagy effect has not been known. The aim of this study was to investigate whether miR-204 regulated autophagy by regulating LC3-II protein, which is the marker of autophagosome during myocardial IR injury.MethodsAdult S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 26 publications
1
89
0
1
Order By: Relevance
“…The pathophysiologic change underlying IR injury involves necrosis and apoptosis. Autophagy is significantly increased in the myocardium after IR and plays an important role in the IR injury [2] . Autophagy is an evolutionarily conserved lysosomal degradative pathway to remove damaged intracellular constituents for the sake of facilitating cellular homeostasis and promoting cell survival under stressed conditions such as nutrient deprivation and hypoxia [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiologic change underlying IR injury involves necrosis and apoptosis. Autophagy is significantly increased in the myocardium after IR and plays an important role in the IR injury [2] . Autophagy is an evolutionarily conserved lysosomal degradative pathway to remove damaged intracellular constituents for the sake of facilitating cellular homeostasis and promoting cell survival under stressed conditions such as nutrient deprivation and hypoxia [3] .…”
Section: Introductionmentioning
confidence: 99%
“…27 miR-204 regulates autophagy through LC3-II. 28 It remains largely unknown as to how autophagy is regulated by miRNAs.…”
mentioning
confidence: 99%
“…Brest et al (26) showed that an miRNA-based alteration in the IRGM gene (encoding a member of the p47 immunity-related GTPase family) regulation can affect the efficacy of autophagy. By studying autophagy induced by ischemia reperfusion, Xiao et al (27) also identified a critical role of miR-204 in regulating autophagy through the LC3-II protein during ischemia reperfusion. However, the role of miRNAs in autophagy-mediated cancer cell chemotherapy resistance remains largely unknown.…”
mentioning
confidence: 99%